The Expansion of the Administrative Court's Jurisdiction in Examining Governmental Factual Actions - Pranoto, Edi; Riyanto, M.; Sunarto, Sunarto; Muawafah, Muawafah (Jurnal Ilmiah Dunia Hukum, 2025)
This study aims to analyze the expansion of the jurisdiction of the Administrative Court (Peradilan Tata Usaha Negara, PTUN) in reviewing factual actions undertaken by administrative officials as an implementation of the rule of law principle in Indonesia. Within the framework of a rule of law state, PTUN functions as a judicial body that ensures oversight of administrative actions that may infringe upon citizens’ rights. Legal developments in the Administrative Government Act (Undang-Undang Administrasi Pemerintahan, UUAP), as regulated in Law No. 30 of 2014 and its amendment through Law No. 6 of 2023 on Job Creation, have expanded the scope of PTUN’s jurisdiction beyond written administrative decisions (Keputusan Tata Usaha Negara, KTUN) to include factual actions by administrative officials. This research employs a qualitative approach through normative legal analysis of statutory provisions and judicial practices to explore the implications of this expanded authority. The findings indicate that this expansion enables greater access to legal protection for citizens, reinforces the supremacy of law, and enhances the accountability of public administration. The study’s main contribution lies in identifying the emerging role of PTUN in overseeing factual actions of government officials, while emphasizing the need for a more comprehensive understanding of its implementation within the framework of Indonesian administrative law.